Mapping of Invasive Species Acacia Decurrens in Part of Mount Merbabu National Park Using Prisma Hyperspectral Imagery - Prayoga, Fuad Rosyadi; Kamal, Muhammad; Arjasakusuma, Sanjiwana (Universitas Lambung Mangkurat, 2024)
Mount Merbabu National Park (TNGMb) is a forest area in the Mount Merbabu. Management and planting changes have caused many changes to the types of plants in TNGMb. Acacia decurrens is an invasive species and its presence in TNGMb can result in a decrease in the diversity of native vegetation types. This research aims to (1) map the distribution of Acacia decurrens plants in TNGMb using PRISMA hyperspectral imagery with the Spectral Angle Mapper (SAM) and Spectral Information Divergence (SID) methods. (2) determine and test the level of accuracy of mapping Acacia decurrens plants in TNGMb using PRISMA hyperspectral imagery. Classification results were carried out using the SAM and SID methods on PRISMA images. The best A. decurrens mapping results were SAM classification at a maximum angle of 0.3 radians with PRISMA Imagery. The distribution of Acacia decurrens in the TNGMb area is in the southwest and northwest. The best accuracy test results were from mapping Acacia decurrens with PRISMA images with an accuracy test value of 56.36%.